Imaging Non-Local Magnetization Dynamics. Issue 3 (3rd May 2016) - von Korff Schmising, C.; Pfau, B.; Schneider, M.; Günther, C. M.; Weder, D.; Willems, F.; Geilhufe, J.; Malm, E.; Müller, L.; Vodungbo, B.; Capotondi, F.; Pedersoli, E.; et al.
Abstract : Many fundamental processes in magnetism take place on a nanometer length and sub-picosecond time scale. An important example of such phenomena in magnetism is ultrafast, spin-polarized transport of laser-excited hot electrons, which is now being recognized as playing a crucial role for novel spintronic devices and for optically induced magnetic switching. Recent experimental examples include the demonstration of all-optical helicity dependent control of spin-polarized currents at interfaces [1 ], the design of novel and efficient terahertz emitters [2 ], and nanoscale spin reversal in chemically heterogeneous GdFeCo driven by non-local transfer of angular momentum [3 ]. In particular, for advanced information technologies with bit densities already exceeding 1 terabit per square inch with bit cell dimensions of (15 × 38 nm 2 ) [4 ], it is of fundamental importance to understand and eventually control the mechanisms responsible for optically induced spin dynamics on the nanoscale.